Transfer to the Local Stroke Center versus Direct Transfer to Endovascular Center of Acute Stroke Patients with Suspected Large Vessel Occlusion in the Catalan Territory (RACECAT): Study protocol of a cluster randomized within a cohort trial. Issue 7 (October 2019) - Abilleira, Sònia; Pérez de la Ossa, Natalia; Jiménez, Xavier; Cardona, Pere; Cocho, Dolores; Purroy, Francisco; Serena, Joaquín; Román, Luis San; Urra, Xabier; Vilaró, Marta; Cortés, Jordi; González, José Antonio; et al.
Rationale: Optimal pre-hospital delivery pathways for acute stroke patients suspected to harbor a large vessel occlusion have not been assessed in randomized trials. Aim: To establish whether stroke subjects with rapid arterial occlusion evaluation scale based suspicion of large vessel occlusion evaluated by emergency medical services in the field have higher rates of favorable outcome when transferred directly to an endovascular center (endovascular treatment stroke center), as compared to the standard transfer to the closest local stroke center (local-SC). Design: Multicenter, superiority, cluster randomized within a cohort trial with blinded endpoint assessment. Procedure: Eligible patients must be 18 or older, have acute stroke symptoms and not have an immediate life threatening condition requiring emergent medical intervention. They must be suspected to have intracranial large vessel occlusion based on a pre-hospital rapid arterial occlusion evaluation scale of ≥5, be located in geographical areas where the default health authority assigned referral stroke center is a non-thrombectomy capable hospital, and estimated arrival at a thrombectomy capable stroke hospital in less than 7 h from time last seen well. Cluster randomization is performed according to a pre-established temporal sequence (temporal cluster design) with three strata: day/night, distance to the endovascular treatment stroke center, and week/week-end day. Study outcome: The primary endpoint is the modified Rankin Scale score at 90 days. The primary safety outcome is mortality at 90 days. Analysis: The primary endpoint based on the modified intention-to-treat population is the distribution of modified Rankin Scale scores at 90 days analyzed under a sequential triangular design. The maximum sample size is 1754 patients, with two planned interim analyses when 701 (40%) and 1227 patients have completed follow-up. Hypothesized common odds ratio is 1.35.